Strategic Analysis of the Implementation of Stakeholder Involvement in Risk Management in Mining and Mineral Companies - Asriani Amiruddin; Bahtiar Usman; Yosephina Purba (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
To analyse the Linkage of Stakeholder Engagement in Risk Management Based on Social License to Operate in Mining and Mineral Companies. This research uses a qualitative approach, to analyse the role of stakeholders in good governance seen from the application of ISO 26000 subject no 7 on Stakeholder Involvement and the issues and strategies applied. The subjects of this research are PT Vale Indonesia IGP Morowali located in Morowali district, Central Sulawesi Province and PT Hengjaya Mineralindo in Morowali district, Central Sulawesi Province. The survey respondent is an employee who has worked in the company for more than three years. This research was analysed using content analysis. Primary data was obtained from interviews and questionnaires distributed to members and administrators who responded. Based on the results of the research analysis, each stakeholder has important roles and activities to maintain the balance between environmental, social, and economic sustainability in the mining and minerals industry. Good engagement and collaboration between all parties can help produce a more positive impact on society and the environment and ISO 26000 Core Subject No. 7 underlines the importance of integrating corporate social responsibility principles in mining and mineral activities, including aspects of risk management.